Malignant hypertension and retinopathy in a western lowland gorilla (Gorilla gorilla gorilla). Issue 4 (20th March 2014) - Niemuth, Jennifer N.; De Voe, Ryan S.; Jennings, Samuel H.; Loomis, Michael R.; Troan, Brigid V.
Abstract Background A 34‐year‐old western lowland gorilla presented with peracute blindness. Methods Clinical evaluation, diagnostic imaging, laboratory analyses, blood pressure measurements, and necropsy were performed. Results The clinical and postmortem findings supported malignant hypertension. Conclusions We describe a case of naturally occurring hypertensive encephalopathy and retinopathy in a gorilla.